Respuesta :
Answer:
[tex]g(x)=6(3)^x[/tex]
Step-by-step explanation:
We are given that
[tex]f(x)=6(\frac{1}{3})^x[/tex]
Function f decreases from quadrant 2 to quadrant 1 and approaches y=0
It cut the y- axis at (0,6) and passing through the point (1,2).
Function g(x) approaches y=0 in quadrant 2 and increases into quadrant 1.
It passing through the point (-1,2) and cut the y-axis at point (0,6).
Reflection across y- axis:
Rule of transformation is given by
[tex](x,y)\rightarrow (-x,y)[/tex]
Using the rule then we get
[tex]g(x)=6(\frac{1}{3})^{-x}=6(3)^x[/tex]
By using
[tex]x^{-a}=\frac{1}{x^a}[/tex]
Substitute x=-1
[tex]g(-1)=6\times (\frac{1}{3})=2[/tex]
Substitute x=0
[tex]g(0)=6[/tex]
Therefore,[tex]g(x)=6(3)^x[/tex] is true.
![Ver imagen lublana](https://us-static.z-dn.net/files/d10/c3f110b28ae7a0455e7275d9e51f0a3e.png)